Deprived minors and cultural heritage: Pedagogical reflections on immersive laboratory experiences - Mancaniello, Maria Rita; Leoncini, Sabina (Form@re - Open Journal per la formazione in rete, 2025)
In juvenile prison settings, juvenile delinquency is a complex issue, where conditions of marginalization and limited access to educational resources can perpetuate antisocial behavior. From this perspective, engaging with cultural heritage takes on strategic pedagogical value, promoting knowledge, culture, and development through cognitive and relational skills. Art, conceived as an experiential and reflective medium, allows adolescents to explore identity, emotions, and self-awareness, fostering processes of meaning-making and critical awareness. In this way, aesthetic experience becomes a tool for inclusion, contributing to the valorization of prison time and the design of cultural interventions capable of supporting the social reintegration of minors. Minori privati della libertà e patrimonio culturale: riflessioni pedagogiche su esperienze laboratoriali nella realtà immersiva. Nei contesti penitenziari minorili, la devianza giovanile rappresenta una questione complessa in cui condizioni di marginalizzazione e accesso limitato a risorse educative possono perpetuare comportamenti antisociali. In tale prospettiva, l’avvicinamento al patrimonio culturale assume una valenza pedagogica strategica, promuovendo conoscenza, cultura e sviluppo attraverso competenze cognitive e relazionali. L'arte, concepita come medium esperienziale e riflessivo, permette agli adolescenti di esplorare identità, emozioni e senso di sé, favorendo processi di costruzione del significato e consapevolezza critica. In tal modo, l’esperienza estetica diviene strumento di inclusione contribuendo alla valorizzazione del tempo della pena e alla progettazione di interventi culturali capaci di sostenere il reinserimento sociale dei minori.